Home / Expert Answers / Advanced Math / convert-the-differential-equation-u-prime-prime-3-u-prime-5-u-e-t-pa985

(Solved): Convert the differential equation \( u^{\prime \prime}-3 u^{\prime}-5 u=e^{t} ...



Convert the differential equation \( u^{\prime \prime}-3 u^{\prime}-5 u=e^{t} \) into a system of first order equations by le???????

Convert the differential equation \( u^{\prime \prime}-3 u^{\prime}-5 u=e^{t} \) into a system of first order equations by letting \( x=u, y=u^{\prime} \) \[ \begin{array}{l} x^{\prime}= \\ y^{\prime}=e^{-5 t}+3 y-5 x \end{array} \]


We have an Answer from Expert

View Expert Answer

Expert Answer


The given differential e
We have an Answer from Expert

Buy This Answer $5

Place Order

We Provide Services Across The Globe